Cervical cancer, a disease of poverty: Mortality differences between urban and rural areas in Mexico - Mauricio Hernández (Salud Pública de México, 2003)
Objective. To examine cervical cancer mortality rates inMexican urban and rural communities, and their associationwith poverty-related factors, during 1990-2000. Material andMethods: We analyzed data from national databases to obtainmortality trends and regional variations using a Poissonregression model based on location (urban-rural). Results.During 1990-2000 a total of 48 761 cervical cancer (CC)deaths were reported in Mexico (1990=4 280 deaths/year;2000=4 620 deaths/year). On average, 12 women died every24 hours, with 0.76% yearly annual growth in CC deaths.Women living in rural areas had 3.07 higher CC mortalityrisks compared to women with urban residence. Comparisonof state CC mortality rates (reference=Mexico City) foundhigher risk in states with lower socio-economic development(Chiapas, relative risk [RR]=10.99; Nayarit, RR=10.5).Predominantly rural states had higher CC mortality ratescompared to Mexico City (lowest rural population). Conclusions.CC mortality is associated with poverty-related factors,including lack of formal education, unemployment, low socioeconomiclevel, rural residence and insufficient access tohealthcare. This indicates the need for eradication of regional differences in cancer detection. This paper is available too at:http://www.insp.mx/salud/index.html